Role of Nitrogen in Tuber Phenol Content and Subsequent Tuber Quality Preservation in Calcium Nitrate-Fertilized Dioscorea Alata Variety Alakisa - Otusanya, M. O. (European Journal of Applied Sciences, 2021)
In a study of proximate, mineral and phenol content in calcium nitrate-fertilized Dioscorea alata variety Alakisa, nitrogen stands out among the two minerals in the fertilizer, in the enhancement of phenol for tuber quality preservation. The experiment was a 3 by 3 factorial arranged in RCBD (randomized complete block design) with 3 replicates and 9 treatment combinations. The mainplot treatment was calcium nitrate soil amendment at the rates 0, 1 and 2 kg ha -1, applied at 3MAP (months after planting). The subfactor treatment was Ca (NO3)2 foliar spray at the rates O, 100 and 500 mg Ɩ-1 applied at 5MAP. Tuber proximate, mineral and phenol content were analyzed in triplicates per treatment and also after incubation with Botryodiplodia theobromae for two weeks. Ca, Mg and K were comparable in the main plot treatments, whereas N, Fe, P and S were significantly higher either in one or both Ca(NO3)2 treatments (1, 2 Kg ha-1) over the control. N, Mg, K and S were comparable in the foliar spray treatments, whereas Fe and P were higher in the 0.6 and 1.2 ml Ɩ-1 foliar spray treatments than the control. Phenol content was higher in the soil amendment treatments (1 and 2 kg ha-1) than the control, but was comparable in the foliar spray treatments. Interaction effects followed similar trends as in the main plot/subplot treatments. Ca correlated significantly with Mg (r = 0.5784). There were significant correlations between Nitrogen (N) and Phenol, S, P, Fe and tuber weight per plant, r = 0.9196, 0.9383, 0.7339, 0.8522 and -0.4602 respectively. S correlated significantly with Fe (r= 0.8502) and P with Phenol, N, S and Fe (r=0.8474, 0.7339, 0.7840 and 0.8130 respectively). Fe and S correlated significantly with Phenol (r = 0.8568 and 0.9758) respectively. Thus N (nitrogen) enhanced phenol as well as 3 other minerals, each of which in turn enhanced tuber phenol content with its antimicrobial potential, for rot resistance and subsequent quality preservation. Significant negative correlations were indicated between crude fibre and Phenol (r = -0.4916), crude fibre and crude protein (r = -0.5975), crude protein and moisture (r = -0.8848). This indicates that as phenol is promoted by the four minerals, this will reduce crude fibre and whereas low crude fibre will promote high crude protein, the latter will promote low moisture. A negative significant correlation has been reported between moisture and shelf life in Dioscorea tubers in literature. Promotion of high crude protein by low crude fibre (r = -0.5975), will also result in high dry matter (r = 0.8848). There was an increase in crude protein across all treatments (soil amendment and folia spray) in the incubated tubers. Dry matter increased across 2 treatment (soil amendment), and 1 treatment (foliar spray) in the incubated tubers, and did not change in the remaining treatments. There was significant correlation between phenol and carbohydrate (r = 0.4350). Carbohydrate is the highest (% dry matter) proximate component, relative to others in variety Alakisa, and because N, P, S and Fe correlated significantly with phenol and phenol with carbohydrate, it was expected that carbohydrate may not change/may increase in the 2 – week incubation. But carbohydrate decreased across all treatments probably because it is also being used up is synthesis of Phenol via the Shikimic pathway as in diseased tissue. Ash which increased across all treatments (soil amendment and foliar spray), had a significant negative correlation (r = -0.4158) with Carbohydrate and thus may have also influenced decrease in Carbohydrate. Fat was the lowest proximate content relative to others and decreased across treatments in the 2 – week incubation. Phenol analysis after the incubation indicated a decrease across all treatments, therefore there ought to be a future trial in which total phenolic compounds (not only phenol) content, as well as minerals and proximate content in calcium nitrate-fertilized variety Alakisa will be monitored in a time-related longer incubation (with B. theobromae) of about 6 to 8 weeks.